2019
DOI: 10.1186/s12967-019-02178-x
|View full text |Cite
|
Sign up to set email alerts
|

ROR2 induces cell apoptosis via activating IRE1α/JNK/CHOP pathway in high-grade serous ovarian carcinoma in vitro and in vivo

Abstract: BackgroundEpithelial ovarian cancer (EOC) is the most lethal cancer in female genital tumors. New disease markers and novel therapeutic strategies are urgent to identify considering the current status of treatment. Receptor tyrosine kinases family plays critical roles in embryo development and disease progression. However, ambivalent research conclusions of ROR2 make its role in tumor confused and the underlying mechanism is far from being understood. In this study, we sought to clarify the effects of ROR2 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Classically, both ROR1 and ROR2, are involved in neurogenesis and embryonic development. Moreover, expression of ROR1 and ROR2 is associated with increased invasion and poor prognosis in numerous cancers [35,36]. Interestingly, in certain cancers, ROR2 expression exhibits tumor-suppressing characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classically, both ROR1 and ROR2, are involved in neurogenesis and embryonic development. Moreover, expression of ROR1 and ROR2 is associated with increased invasion and poor prognosis in numerous cancers [35,36]. Interestingly, in certain cancers, ROR2 expression exhibits tumor-suppressing characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does ROR2 possess tumor-suppressing traits but is also implicated in inducing apoptosis through the EnRS pathway. Recently, ROR2 promoted apoptosis in ovarian carcinoma through the induction EnRS sensing protein, inositol requiring enzyme-1α (IRE1α) and downstream C/EBP homologous protein (CHOP) [35,36]. Thus, ROR2 overexpression observed in response to TVB and tamoxifen treatment could be illustrating tumor-suppressing characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms described implicate the activation of the Rho-family of small GTPases [ 39 ] or the upregulation of c-myc, Cyclin D1, Cyclin E, and CDK4 [ 40 ], and PCNA and CDK1 [ 12 ]. In contrast, other studies showed that ROR2 inhibited proliferation in gastric [ 26 ], colorectal [ 23 ], and ovarian cancer [ 41 ], as well as in esophageal squamous cell carcinoma [ 42 ]. However, these studies relied only on ectopic expression of ROR2 [ 26 , 41 , 42 ] or provided inconsistent results between overexpressing and silencing experiments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation regulators MKI67 (Figure 6C) and MAP2K4 (Figure 6D) were altered upon MEV treatment [44,55]. Apoptosis regulator ROR2 [56] was significantly upregulated in 72 h MEVs treated cells compared to untreated (Figure 6E). ROR2 is also known to participate in negative regulation of Wnt signalling activity.…”
Section: Treatment Of Bovine Milk-derived Extracellular Vesicles Induced Cellular Senescence In Neuroblastoma Cellsmentioning
confidence: 97%